2019
DOI: 10.1051/0004-6361/201834281
|View full text |Cite
|
Sign up to set email alerts
|

Lower atmosphere and pressure evolution on Pluto from ground-based stellar occultations, 1988–2016

Abstract: Context. The tenuous nitrogen (N2) atmosphere on Pluto undergoes strong seasonal effects due to high obliquity and orbital eccentricity, and has recently (July 2015) been observed by the New Horizons spacecraft. Aims. The main goals of this study are (i) to construct a well calibrated record of the seasonal evolution of surface pressure on Pluto and (ii) to constrain the structure of the lower atmosphere using a central flash observed in 2015. Methods. Eleven stellar occultations by Pluto observed between 2002… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 42 publications
5
36
3
Order By: Relevance
“…The model includes atmospheric dynamics and transport, turbulence, radiative transfer and molecular conduction as well as phase changes for N 2 , CH 4 and CO. The GCM reproduces well the thermal structure measured by the New Horizons spacecraft in the lower atmosphere (below 200 km altitude) and the threefold increase in surface pressure observed from stellar occultations between 1988 and 2015 with~1.1 Pa in 2015 5,22 . Recent improvements to the model include incorporation of perennial high-altitude CH 4 deposits in the equatorial regions (bladed terrain), based on mapping of Pluto's far side 18 , and the use of the latest topography from New Horizons data 9 .…”
Section: Methodssupporting
confidence: 65%
“…The model includes atmospheric dynamics and transport, turbulence, radiative transfer and molecular conduction as well as phase changes for N 2 , CH 4 and CO. The GCM reproduces well the thermal structure measured by the New Horizons spacecraft in the lower atmosphere (below 200 km altitude) and the threefold increase in surface pressure observed from stellar occultations between 1988 and 2015 with~1.1 Pa in 2015 5,22 . Recent improvements to the model include incorporation of perennial high-altitude CH 4 deposits in the equatorial regions (bladed terrain), based on mapping of Pluto's far side 18 , and the use of the latest topography from New Horizons data 9 .…”
Section: Methodssupporting
confidence: 65%
“…(Bertrand and Forget, 2016;Bertrand et al, 2018Bertrand et al, ,2019. The initial state used for the 3D GCM was selected among many possible results on the basis of their agreement with the observed pressure evolution and the distribution of surface ices in 2015 (Meza et al, 2019;Schmitt et al, 2017). We start the GCM simulation in 1984, in order to reach established methane and CO atmospheric cycles in equilibrium with the surface reservoir (Forget et al, 2017).…”
Section: Simulation Settings For the Pluto Gcmmentioning
confidence: 99%
“…This was initially modeled for Triton and Pluto (see reviews by Spencer et al 1997 andYelle et al 1995). Since those reviews, trends of increasing atmospheric pressure for both Triton and Pluto were observed using the technique of stellar occultation, with an increase by factors of two and three respectively (Elliot et al 1998;Elliot et al 2000;Elliot et al 2003a;Olkin et al 1997Olkin et al , 2015Meza et al 2019; see section 6). The new time-base of atmospheric observations and the New Horizons flyby of Pluto inspired new models of seasonal variation (e.g., Young 2012Young , 2013Young , 2017Hansen et al 2015;Olkin et al 2015), including general circulation models (e.g., Forget et al 2017) and evolution of atmospheres on the timescale of millions of years (e.g., Bertrand et al 2016Bertrand et al , 2018.…”
Section: Variation Of Atmospheres Over An Orbitmentioning
confidence: 99%
“…Observations in 2002 showed a doubling of the pressure since 1988 (Sicardy et al 2003;Elliot et al 2003a). Many high-quality observations since have revealed the continued changes in Pluto's atmosphere, its thermal structure, and waves (Young et al 2008;Toigo et al 2010;Sicardy et al 2016;Dias-Oliveira et al 2015;Pasachoff et al 2017;Meza et al 2019). The New Horizons radio and solar occultations revealed N 2 in vapor-pressure equilibrium with the N 2 -rich ice, an overabundance of gaseous CH 4 possibly explained by CH 4 -rich patches, hazes and photochemical products, a cold upper atmosphere, and an atmospheric escape rate dominated by CH 4 and much smaller than expected (See Spencer et al 2019, this book, andGladstone &.…”
Section: Insert Fig 7 Herementioning
confidence: 99%